Copper Tolerance and Accumulation on Pelargonium graveolens L'Hér. Grown in Hydroponic Culture - Chrysargyris, Antonios; Maggini, Rita; Incrocci, Luca; Pardossi, Alberto; Tzortzakis, Nikos G. (My University, 2021)
Heavy metal contamination is a major health issue concerning the commercial production of medicinal and aromatic plants (MAPs) that are used for the extraction of bioactive molecules. Copper (Cu) is an anthropogenic contaminant that, at toxic levels, can accumulate in plant tissues, affecting plant growth and development. On the other hand, plant response to metal-induced stress may involve the synthesis and accumulation of beneficial secondary metabolites. In this study, hydroponically grown Pelargonium graveolens plants were exposed to different Cu concentrations in a nutrient solution (4, 25, 50, 100 μM) to evaluate the effects Cu toxicity on plant growth, mineral uptake and distribution in plants, some stress indicators, and the accumulation of bioactive secondary metabolites in leaf tissues. P. graveolens resulted in moderately tolerant Cu toxicity. At Cu concentrations up to 100 μM, biomass production was preserved and was accompanied by an increase in phenolics and antioxidant capacity. The metal contaminant was accumulated mainly in the roots. The leaf tissues of Cu-treated P. graveolens may be safely used for the extraction of bioactive molecules.
Keywords: Antioxidants; Bioaccumulation; Copper toxicity; Hydroponics; Translocation factor